(untitled) (Economic and Political Thought, 2014)
The majority of enterprises in the world are conventionally managed. However, there are companies managed unconventionally, which achieve excellent results. One of them is for example Mumbai Tiffin Box Suppliers Association, an Indian company known as Dabbawala. It employs mainly illiterates, is a very simple structure and makes only one mistake in 8 million deliveries. Another unconventional company is Semco, a Brazilian enterprise using ‘radical democratic solutions’. Other firms are American W.L. Gore & Associates and Morning Star. The former gives its employees complete freedom and triggers their extraordinary involvement. The latter promotes self-management. Other firms managed unconventionally include the Spanish Banco Popular, organised in the form of a reversed pyramid, and the Polish branch of a British firm – Hays, placing extreme trust in the employees. All these companies achieve extraordinary results.